A PERFORMANCE EVALUATION USING BALANCED SCORECARD (A Case Study on Unit Gemilang in Tupperware PT Adicitra Prima Kencana Malang City) - Aliffia Yulitarahmi SE (Jurnal Ilmiah Mahasiswa FEB, 2019)
This research aims to discover the performance of Gemilang unit Tupperware PT Adicitra Prima Kencana Malang and evaluate it using Balanced Scorecard method from Financial Performance (3 measuring rods), Customer (1 measuring rod), Internal Business (3 measuring rods), and Learning and Growth (4 measuring rods). This research employed descriptive quantitative approach and data collection method is done through interview, documentation, and questionnaire with purposive sampling. For Customer Perspective, the samples are 50 respondents who already made transactions under Gemilang unit, and for Learning and Growth the samples are 17 employees of Tupperware PT Adicitra Prima Kencana. Furthermore the data are processed through the SPSS software ver. 25. Whilst, data collection for Financial Perspective and Internal Business Perspective proceeded from primer and secondary data. In conclusion, Gemilang unit Tupperware PT. Adicitra Prima Kencana Malang  is in a GOOD ENOUGH condition.Keywords: Balanced Scorecard, Performance Measurement